Perancangan Website Profil Perusahaan Menggunakan Metode Waterfall Pada PT. Putu Marta Mandiri - Arrafi, Bintang; Abdi Virgiansyah, Ferdinand; Alfarizi, Salman; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
In facing the dynamics of this complex industry, practical work on the theme of designing the profile of a specialist gas construction company is becoming increasingly important. PT. Putu Marta Mandiri which operates in the gas specialist construction sector. The data analysis techniques used in this research are observation, interviews and literature study. The design was carried out using the UML (Unified Modeling Language) modeling approach, including use case diagrams, activity diagrams, sequence diagrams and class diagrams. The company profile website is designed with main features such as home page, company profile, services, team, partnerships, location, gallery and contact. System testing is carried out using the black box testing method to validate functionality and ensure the system runs according to expected specifications.